Star formation in the starburst cluster in NGC 3603 - Correnti, Matteo; Pang, Xiaoying (Astrophysics and space science, 2012)
We have used new, deep, visible and near infrared observations of the compact starburst cluster in the giant HII region NGC 3603 and its surroundings with the WFC3 on HST and HAWK-I on the VLT to study in detail the physical properties of its intermediate mass (∼1-3 M⊙) stellar population. We show that after correction for differential extinction and actively accreting stars, and the study of field star contamination, strong evidence remains for a continuous spread in the ages of pre-main sequence stars in the range ∼2 to ∼30 Myr within the temporal resolution available. Existing differences among presently available theoretical models account for the largest possible variation in shape of the measured age histograms within these limits. We also find that this isochronal age spread in the near infrared and visible Colour-Magnitude Diagrams cannot be reproduced by any other presently known source of astrophysical or instrumental scatter that could mimic the luminosity spread seen in our observations except, possibly, episodic accretion. The measured age spread and the stellar spatial distribution in the cluster are consistent with the hypothesis that star formation started at least 20-30 Myrs ago progressing slowly but continuously up to at least a few million years ago. All the stars in the considered mass range are distributed in a flattened oblate spheroidal pattern with the major axis oriented in an approximate South-East-North-West direction, and with the length of the equatorial axis decreasing with increasing age. This asymmetry is most likely due to the fact that star formation occurred along a filament of gas and dust in the natal molecular cloud oriented locally in this direction.